PELAKSANAAN PENDAMPINGAN PENERIMA MANFAAT DI BALAI REHABILITASI SOSIAL ANAK YANG MEMERLUKAN PERLINDUNGAN KHUSUS (BRSAMPK) RUMBAI KELURAHAN MERANTI PANDAK KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Dafit Dafersia; Wilson Wilson; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study uses qualitative research with a descriptive approach. Research subjects are young social workers social workers, and first social workers, and informal controls (children). Data collection through observation, interview, and documentation techniques. The number of child offenders from January to 3 May 2020 totaled 30 children with different cases. And 10 children are victims of underage violence. An interview guide containing 14 questions about the implementation of beneficiary assistance. With sub focus what approach is chosen, identify problems, formulate and determine the program, Involve the client to participate in dealing with problems and overcome them, the implementation of planning, program evaluation, termination of relations with clients with 1-2 sub indicators. The results showed that the implementation of beneficiary assistance had several stages, namely the preparation phase, the assessment stage, the alternative planning stage of the program or activity, the stage of formulating the action plan, the implementation stage, the evaluation stage, and the termination stage. Social Workers At the same time as a second parent, assistance can also help resolve children's cases and can influence children's behavior. In mentoring children get educational assistance in the form of vocational training, spiritual, physical, social, and psychosocial guidance which is beneficial when the child leaves the hall.Key Words: Implementation, Assistance, Beneficiaries